2008
DOI: 10.1248/yakushi.128.141
|View full text |Cite
|
Sign up to set email alerts
|

Functional Saponins in Tea Flower (Flower Buds of <i>Camellia sinensis</i>): Gastroprotective and Hypoglycemic Effects of Floratheasaponins and Qualitative and Quantitative Analysis Using HPLC

Abstract: As a part of our characterization studies on the bioactive saponin constituents of tea ‰owers (Camellia sinensis, ‰ower buds), the methanolic extract and 1-butanol-soluble portion (the saponin fraction) from the ‰ower buds were found to exhibit potent inhibitory eŠects on ethanol-and indomethacin-induced gastric mucosal lesions in rats and on serum glucose elevation in sucrose-loaded rats. Among the constituents of the 1-butanol-soluble portion, ‰oratheasapo-nins A, B, and C showed gastroprotective and hypogly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 36 publications
0
47
0
Order By: Relevance
“…Furthermore, because RL-TGR seems to be specifically expressed in fish, this coreceptor in fish might have coevolved with the triterpene glycoside compounds found in their potential prey organisms. Triterpene glycosides are closely related to steroidal glycosides and saponins, which are found in a variety of marine and terrestrial organisms (20,30,31,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). Thus, RL-TGR and related receptors might serve as detectors of these classes of compounds, and other RAMP-like coreceptors might have evolved as detectors of other chemical defenses.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, because RL-TGR seems to be specifically expressed in fish, this coreceptor in fish might have coevolved with the triterpene glycoside compounds found in their potential prey organisms. Triterpene glycosides are closely related to steroidal glycosides and saponins, which are found in a variety of marine and terrestrial organisms (20,30,31,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). Thus, RL-TGR and related receptors might serve as detectors of these classes of compounds, and other RAMP-like coreceptors might have evolved as detectors of other chemical defenses.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] The 1 H-(pyridined 5 ) and 13 C-NMR (Table 5) Next, we examined the gastroprotective effects of the principal constituents (6, 7, 8, gallic acid) from the flower buds of C. oleifera and the flavonoid constituents (6, 7) were found to show moderate activities as shown in Table 6. On the other hand, we have reported the isolation and structure elucidations of acylated polyhydroxyoleanane-type oligoglycosides with potent gastroprotective activities from several medicinal flowers or medicinal foodstuffs: that is, escins (Aesculus hippocastanum, seeds), 36) theasaponins (Camellia sinensis, seeds), 27) assamsaponins (Camellia assamica, seed and leaves), 37) floratheasaponins (Camellia sinensis, flower buds), 7) and camelliosides (Camellia japonica, flower buds). 11) With regard to the relationships between the saponin structures and gastroprotective activities, the acyl groups at the 21-and 22-positions of the polyhydroxyoleanane-type triterpene part and the 3-O-glucuronide structure were found to be essential.…”
Section: Biological Activities Of the Extract And Fractionsmentioning
confidence: 99%
“…However, the chemical constituents and biological activities of the flower buds of this plant have not yet characterized. Recently, we have reported the isolation and structure elucidation of acylated polyhydroxyoleanane-type triterpene oligoglycosides from the flower buds of C. sinensis 1,[5][6][7][8][9] and C. japonica. 10,11) Furthermore, those oligoglycosides were found to exhibit antiallergic, 6) antidiabetic, 7) antiobesitic, 5,8) gastroprotective, 7,10,11) and platelet aggregation 10,11) activities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some alkaloids have been reported to have gastroprotective effects (Gadekar et al, 2010;Hariprasath et al, 2012;Nwidu and Nwafor, 2009). Tannins have also been reported to contribute immensely in gastroprotection (Dragana et al, 2009;Vasconcelos et al, 2010) while some saponins also protect the gut from ulcerogenic agents (Yoshikawa et al, 2008;Nwidu and Nwafor, 2009). A study conducted in Siqueira et al (2012), had reported the role of terpinoids in the prevention of ulcer and the healing of existing ulcers.…”
Section: Discussionmentioning
confidence: 99%